'Hope for a Celestial City - A Triptych': A musical composition for sustainability and cleaner productions for the Jing-Jin-Ji region, China. (1st January 2017) - Casazza, Marco; Ferrari, Carlotta; Liu, Gengyuan; Ulgiati, Sergio
Abstract: The construction of better alternatives to the present lifestyles and the solution of the environmental problems generated by modern economies and intensive exploitation of natural resources certainly require better science and technology. However, it is very unlikely that the needed global and complex solutions may be provided by one disciplinary field only, although very important, as science is. Solutions require broad minded approaches and comprehensive understanding of the multi-dimensionality of life on earth. A variety of tools and ways to approach the transition towards a cleaner and healthier environment is needed, not only to capture the complexity of life expressions, but also to value and appreciate the complexity of languages, narratives and points of view (scientific, artistic, economic, social, among others) that may lead to the "Celestial City", a metaphor for better ways of living. This work explores the meaning and the potential contribution of a musical piece, representative of art and social languages, to inspire a transition process, with specific focus on Jing-Jin-Ji (JJJ) region, China. The piece is the 'Hope for a Celestial City – A Triptych' is a three-sections work for solo violin, composed by Carlotta Ferrari. It is inspired by the designed future 'urban' agglomerations such as the urbanised region of Jing-Jin-Ji, China. The piece refers to Bunyan's 'Celestial City' (this expression refers to 'The Pilgrim's Progress', written by John Bunyan in 1678) as a way to reflect on the past, present and future of JJJ. The work is inspired by three sets of quotes. Each of them is divided in two sub-sections: the first one is referred to as 'literature quote', which serves also as non-scientific reference for each section of the musical composition; the second one, on the other side, contains a set of scientific and technical references to guide and base the inspiration of the music. The first part of the piece represents the arrogant industrial civilization, "humans subdue nature", with a particular attention to JJJ. The second part is focused on puzzling and soul-searching energy and work. In particular, the concept is that human activities can be either harmful or beneficial both for the environment and for elevating the society. The third part represents the 'pilgrimage' of human life and activities towards a different city: the Celestial City, where efforts achieve the result of harmonious and sustainable life. In other words, a more sustainable city can be built by transforming the present urban systems from competition to cooperation within and beyond Jing-Jin-Ji region borders. Implementing control targets, optimizing industrial structures and infrastructures, and achieving both coal consumption and air pollution reduction are seen as important technical steps towards more equitable and fulfilling life, where new patterns of connection, interaction, and exchange among residents are achieved within a healthier urban environment. The use of aesthetic inquiry, multiple languages and new creative approaches represents a support for accelerating the transition toward a more sustainable and equitable post fossil-carbon society, in particular in the case of expanding urban agglomerations. This work represents a methodological approach to artistic engagement trough music creation and performance. The purpose of such a process is to generate a collective reflection and to produce a transformative power. The collective reflection is stimulated by music performance. Furthermore, this is a way to include the contribution of artists into an important sustainability issue. Finally, this work demonstrates that music can support the communication of scientific messages, which could be difficult to be delivered in their original science form. Highlights: This paper explores an approach to deliver a sustainability message through music. Music performance can be an instrument of engagement trough focused meditation. Music can be a form of societal engagement of artists for supporting sustainability. Music can support the communication of complex scientific messages.